Evaluation of Information Communication technology projects in developing world: formulating a prospective methodology - N. Meera Shaik; D.U.M. Rao (Journal of Agricultural Extension Management, 2025)
A new paradigm of agricultural development is emerging. The overall development of rural areas in the developing countries is taking new avenue of expansion. The old ways of doing business in terms of delivery of important services to citizens are being challenged in both the developing and developed countries. A complete transformation of traditional societies to knowledge societies has been increasingly felt all over the world. The report of the "Task Force on India as Knowledge Super Power (2001)" emphasizes the need for developing the capacity to generate, absorb, disseminate and protect knowledge and to exploit knowledge as a powerful tool to derive societal transformation. The background report of "working Group on Information Technology for the Masses" declares: "It is the firm view of the Government that if any technology can create new opportunities to bridge the gap between information haves and have-nots in the present times, it is Information Technology". (Working Group of GOI, 2000). It is being increasingly felt that Information Communication Technology (ICT) can be a major vehicle for all round socio-economic development. ICT can play a spectacular role in societal transformation to realize the concept of "Knowledge Society" in the Indian context